2009
DOI: 10.1007/s10140-009-0829-3
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic coronary angiography in patients with surgically treated type A aortic dissection: preliminary results

Abstract: Acute type A aortic dissection is a serious emergency with a mortality rate of up to 40% within the first 24 h when left untreated. Surgical therapy needs to be initiated promptly. Due to this urgent situation, preoperative evaluation of the coronary arteries is not routinely performed in these patients. The aim of this study was to evaluate the accuracy of 64-slice computed tomography angiography (CTA) for postoperative coronary artery assessment in these patients. Ten consecutive patients with two or more ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…40) Rosskoph et al compared the CT angiography and CAG and reported the sensitivity, specificity, positive and negative predictive value was 33%, 99%, 50%, and 99%, respectively. 41) CT assessment has greatly reduced invasiveness and time delay before surgery. However, it is questionable whether additional CT angiography for assessment of coronary involvement is essential in patients with the definite diagnosis of AAAD.…”
Section: Coronary Arterymentioning
confidence: 99%
“…40) Rosskoph et al compared the CT angiography and CAG and reported the sensitivity, specificity, positive and negative predictive value was 33%, 99%, 50%, and 99%, respectively. 41) CT assessment has greatly reduced invasiveness and time delay before surgery. However, it is questionable whether additional CT angiography for assessment of coronary involvement is essential in patients with the definite diagnosis of AAAD.…”
Section: Coronary Arterymentioning
confidence: 99%
“…AD is an acute life-threatening emergency condition that frequently has a fatal outcome [ 16 ]. Early diagnosis and treatment are essential to improve prognosis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%